Sanitary standards in seeds (Research, Society and Development, 2022)
The seed is the input with the highest added value, as it contains the genetic constitution of the variety. Where the maximum agricultural productivity potential is determined by the genetic potential. Therefore, increasingly, understanding the issue of seed health has become fundamental in order to further increase agricultural productivity and competitiveness in the country. Thus, among the production factors inherent to the cultivation of agricultural species, seed health becomes an important and growing issue at the time of management definition, considering its influence on the establishment and development of crops. The sanitary factors are characterized by providing deleterious effects caused by microorganisms and insects when present in the seeds. In this sense, the present work aims to describe the characterization of sanitary standards for seed production and studies on the current legislation for carrying out sanitary tests.